Zone of Proximal Development Perspektif Lev Vygotsky dalam PAI Kontemporer melalui Project Based Learning - Siti Nurhalimah; Alfi Rahmi (Lembaga Yasin AlSys, 2026)
Contemporary Islamic Religious Education (PAI) learning faces challenges in internalizing Islamic values because teacher-centered learning remains dominant. Although the Zone of Proximal Development (ZPD) theory and Project-Based Learning (PjBL) have been widely studied, the integration of the two in PAI learning still requires conceptual strengthening. This study aims to analyze the implementation of Lev Vygotsky’s Zone of Proximal Development theory through the Project-Based Learning method in contemporary Islamic Religious Education learning. This study used a qualitative approach with a library research design. The data sources consisted of books, journal articles, and scientific documents selected purposively based on relevance, credibility, and publication recency. Data were collected through documentation study and analyzed using content analysis techniques. The results showed that the integration of ZPD and PjBL was able to realize learner-centered learning through scaffolding, social interaction, and contextual learning experiences. This approach contributes to improving learning motivation, critical thinking skills, collaboration, communication, internalization of Islamic values, and the formation of students’ religious character. These findings strengthen the relevance of social constructivist theory in the development of PAI learning and broaden understanding of the integration of ZPD and PjBL in the context of Islamic education. The conclusion of this study affirms that the integration of ZPD and PjBL can serve as a conceptual alternative in designing PAI learning that is more contextual, collaborative, and meaningful. The implications of this study include theoretical contributions to the development of PAI learning models based on social constructivism as well as practical contributions for teachers and curriculum developers in designing learning that is oriented toward students’ active engagement.